Fewer gastrointestinal bleeds with ticagrelor and prasugrel compared with clopidogrel in patients with acute coronary syndrome following percutaneous coronary intervention. Issue 4 (13th July 2020) - Abraham, Neena S.; Yang, Eric H.; Noseworthy, Peter A.; Inselman, Jonathan; Yao, Xiaoxi; Herrin, Jeph; Sangaralingham, Lindsey R.; Ngufor, Che; Shah, Nilay D.
Summary: Background: Gastrointestinal bleeding (GIB) frequently occurs following percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) with the prescription of P2Y12 inhibiting antiplatelet agents. Compared with clopidogrel, the newer P2Y12 inhibitors lower major adverse cardiac events with similar or possibly higher major bleeding events. The comparative GIB rates of these medications remain poorly understood. Aim: To compare GIB rates associated with clopidogrel, prasugrel and ticagrelor using national medical and pharmacy claims data from privately insured and Medicare Advantage enrollees . Methods: Propensity score and inverse probability treatment weighting were used to balance baseline characteristics among treatment groups. The 1‐year GIB risk was calculated using weighted Cox proportional hazard models and expressed as hazard ratios (HR) with 95% confidence intervals (CI) and number needed to harm (NNH). Results: We identified 37 019 patients with ACS (non‐ST elevation ACS [NSTE‐ACS] and ST‐elevation myocardial infarction [STEMI]) within 14 days of a PCI (mean age 63 years and 70% male). Clopidogrel prescription was most common (69%) with prasugrel (16%) and ticagrelor (14%) prescribed less frequently. When compared with clopidogrel, ticagrelor was associated with a 34% risk reduction (HR 0.66; 95% CI: 0.54–0.81) in GIB overall and with NSTE‐ACS, and a 37% GIB risk reduction (HR 0.63; 95% CI: 0.42–0.93) in STEMI patients. When compared with clopidogrel, prasugrel was associated with a 21% risk reduction (HR 0.79; 95% CI: 0.64–0.97) overall, a 36% GIB risk reduction (HR 0.64; 95% CI: 0.49–0.85) in STEMI patients but no reduction of GIB risk in NSTE‐ACS patients. Conclusions: In the first year following PCI, ticagrelor or prasugrel are associated with fewer GIB events than clopidogrel.